Inactivation of endothelial adenosine A2A receptors protects mice from cerebral ischaemia‐induced brain injury. (21st May 2019) - Zhou, Yaqi; Zeng, Xianqiu; Li, Ge; Yang, Qiuhua; Xu, Jiean; Zhang, Min; Mao, Xiaoxiao; Cao, Yapeng; Wang, Lina; Xu, Yiming; Wang, Yong; Zhang, Yu; et al.
Abstract : Background and Purpose: Inactivation of the gene for adenosine A2A receptors (ADORA2A for humans and Adora2a for rodents) protects against brain injury in experimental stroke. However, the cell‐specific pathogenic effects of A2A receptors in thromboembolic stroke and the underlying mechanisms remain undefined. Here, we tested the hypothesis that inhibition of endothelial A2A receptors after thromboembolic stroke improves post‐stroke outcomes via down‐regulation of inflammation. Experimental Approach: Thromboembolic stroke was induced by embolic middle cerebral artery occlusion in mice. Post‐stroke outcomes were determined with neurological deficit scoring, infarct volume, inflammatory marker expression, brain leukocyte infiltration, blood–brain barrier (BBB) leakage, and oedema assessment. Anti‐inflammatory effects of silencing the gene for A2A receptors or pharmacological antagonism of these receptors were assessed in vitro. Key Results: Thromboembolic stroke induced Adora2a expression in the brain. Mice globally deficient in Adora2a ( Adora2a −/− ) were resistant to stroke injury. Mice specifically deficient in endothelial Adora2a ( Adora2a ΔVEC ) showed reduced leukocyte infiltration, BBB leakage, and oedema after stroke, along with attenuated downstream proinflammatory markers, both in vivo and in vitro. The A2A receptor antagonist, KW 6002, also reduced brain injury and inflammation after stroke. Inactivation of ADORA2A inhibited endothelial inflammation via suppression of the NLRP3 inflammasome, down‐regulating cleaved caspase 1 and IL‐1β expression. Conclusions and Implications: Specific inactivation of endothelial A2A receptors mitigated ischaemic brain injury and improved post‐stroke outcomes, at least partly, through anti‐inflammatory effects via blockade of NLRP3 inflammasome activity. Our findings may open new approaches to vascular protection after ischaemic stroke.